Are Women Better Bankers to the Poor? Evidence from Rural Microfinance Institutions - Valentina Hartarska; Denis Nadolnyak; Roy Mersland (American Journal of Agricultural Economics, 2014)
Microfinance Institutions (MFIs) provide financial services to the poor and in many ways resemble both banks and non-profit organizations. Many MFIs target women because more women than men are poor, especially in rural areas. Studies show that women manage money differently from men and have different leadership styles. Thus, in credit unions and financial firms, female and male managers achieve different results. In microfinance, gender diversity on the board of MFIs is beneficial, and loans authorized by female loan officers have lower default rates. Motivated by these findings, we ask whether MFIs with a female Chief Executive Officer (CEO) are more efficient at serving the poor without jeopardizing financial sustainability. We adapt the banking approach to managerial (in)efficiency to account for the outreach and sustainability goals of the MFIs, and evaluate whether MFIs' outreach efficiency differs by the gender of their respective CEOs. We estimate a stochastic frontier cost function using the Battese-Coelli (1995) model and the “true” random effects estimators using panel data from over 250 MFIs. We find that MFIs with female CEOs have significantly higher outreach efficiency than MFIs with male CEOs. Similar results are found with a two-step stochastic frontier approach. Overall, the results suggest that promoting gender diversity at the top levels of MFI management is likely to have both social and financial benefits.
Keywords: 650